A circular frame designed to hold the pot - Mumbai Archive Project Team (Jio Institute, 2024)
A circular frame is designed to hold the pot, decorated with floral garlands and mango leaves. Fruits and vegetables donated by villagers are also part of the decor. These would be distributed as prasada after the event.